A Study On Perceived Risk, Frugal Shopping and Perceived Enjoyment that Affect Customer Attitude To Accept Toy and Equipment Renting For Children - Devanny Gumulya (Jurnal Manajemen dan Pemasaran Jasa, 2020)
The industrialisation and urbanisation have made goods affordable and quickly to obtain. These create  hyper-consumption where we are used to buying more than we need, and so fast discarding the things that we buy. Access-based consumption is a trend that gains more popular in today society, in which consumer can have access to new and various items without having to own them. One of access-based consumption is renting, and this concept has been applied in many sectors such fashion, property and recently applied in items for children, as now more Millenials are living in limited space, so they really need to very critical in choosing which product to own. The study aims to research the relationship between perceived risk, frugal shopping, perceived enjoyment and attitude toward renting items for children. The online questionnaire was administered to 100 participants. The results showed that psychological risk affects attitude negatively, perceived enjoyment affect attitude positively, and frugal shopping affects perceived enjoyment and attitude positively. Marketing strategies are suggested for renting business owners by embracing the enjoyment feeling from renting as follows: promoting that by renting consumer’s house will less clutter with unwanted items; the benefit of getting new items regularly without having to buy; the benefit of playing and using items beyond their usual shopping budget; and that by renting the lifetime of one item is maximized.